1982
DOI: 10.1136/adc.57.6.410
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in the development of intraventricular haemorrhage in the preterm neonate.

Abstract: Real-time ultrasound is a safe and non-invasive method of diagnosing intraventricular haemorrhage (IVH) with a high degree of accuracy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
125
0
10

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(144 citation statements)
references
References 32 publications
9
125
0
10
Order By: Relevance
“…Although several other investigators observed significant univariate associations between IVH in premature infants and specific maximum PaCO 2 cutoff values: >45 mm Hg, 11 X50 mm Hg, 8 >60 mm Hg, 11,15,16 and >65 mm Hg, 10 in multivariate analyses a significant association was not found. 10,11,15 Only one small observational trial using multivariate analysis found that hypercapnia was a statistically significant antecedent to IVH. 12 In contrast, three trials found no association between hypercapnia and IVH.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although several other investigators observed significant univariate associations between IVH in premature infants and specific maximum PaCO 2 cutoff values: >45 mm Hg, 11 X50 mm Hg, 8 >60 mm Hg, 11,15,16 and >65 mm Hg, 10 in multivariate analyses a significant association was not found. 10,11,15 Only one small observational trial using multivariate analysis found that hypercapnia was a statistically significant antecedent to IVH. 12 In contrast, three trials found no association between hypercapnia and IVH.…”
Section: Discussionmentioning
confidence: 73%
“…4 Further, hypercapnia in animals has been shown to abolish intact cerebral autoregulation. 5,6 In addition to low gestational age, low birth weight, male gender, worse acute lung disease, etc., hypercapnia has also been identified as an important risk factor for intraventricular hemorrhage (IVH), [7][8][9][10][11][12][13][14][15][16] the most common acute brain injury of premature infants. Although it is unclear whether hypercapnia causes IVH or results from circulatory disturbances that follow severe IVH, hypercapnia may influence the development of IVH by causing vasodilation of cerebral resistance arterioles, increasing CBF, and by impairing intact cerebral autoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a consecutive series of infants with IVH diagnosed by a single criterion (excluding autopsy) was available for a cohort study. US by sector scanner through the anterior fontanelle has been accepted as a reliable method for detecting IVH [16] although results have been reported to be equivocal in a small number of infants [14]. Classification of increases in density in the region of the head of the caudate appears to be the most important weakness of the US.…”
Section: Discussionmentioning
confidence: 99%
“…There are several etiologies that can be grouped in four categories: prenatal (congenital), perinatal, postnatal, and unclassifiable 14 . In preterm newborns the main cause is intraventricular heamorrhage usually occuring in the first days of life 3,21 , while in infants born at term the most common is brain maldevelopment 3 .…”
Section: Discussionmentioning
confidence: 99%